ANALISIS MANAJEMEN SUMBER DAYA MANUSIA PENGAJAR ALQURAN METODE QIROATI PADA JENJANG DASAR - Alfirdaus, Hamdan; Fahyuni, Eni Fariyatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
HR management is the systematic handling of problems related to personnel, including workers, supervisors and other staff members, with the aim of facilitating the operations of an organization or institution to achieve predetermined goals. This research aims to find out how human resource management is related to the planning process, recruitment and selection process, development process and also the evaluation process of qiroati method teachers whose students are at the basic level at TPQ Riyadhul Ghofur in an effort to achieve success in producing a generation of students who excel in Reciting Al-Qur'an. This research is classified as qualitative research with a qualitative descriptive approach because it relies mostly on data obtained from observations and interviews with individuals. This research was conducted on Monday 24 March 2024 at TPQ Riyadul Ghofur involving the chairman of TPQ as the sole and main resource person. The research results show that: First, the TPQ chairman prepares the requirements for prospective Al-Quran teachers, then meets first with the institution's management. Second, the recruitment and selection process is carried out by accepting teaching candidates who already have the Qiroati creed with the criteria of being patient, firm, disciplined and passionate about teaching. Third, TPQ always includes branch MMQ development activities every 3 months and sub-districts every 1 month which contains Tadarus juz 1-30 khataman activities and teaching quality development. Fourth, the TPQ Evaluation Process involves familiarizing Al-Quran teachers before entering the class with briefings and performance evaluations on the spot while the lesson is taking place.